2022
DOI: 10.1063/5.0096877
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of drug dissolution in the human stomach: Effects of posture and gastroparesis on drug bioavailability

Abstract: The oral route is the most common choice for drug administration because of several advantages such as convenience, low cost, and high patient compliance, and the demand and investment in research and development for oral drugs continue to grow. The rate of dissolution and gastric emptying of the dissolved active pharmaceutical ingredient (API) into the duodenum is modulated by gastric motility, physical properties of the pill, and the contents of the stomach, but current in-vitro procedures for assessing diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…However, for all cases, initially there is an exponential rise which changes into a linear growth that eventually asymptotes to a value as t → ∞. The figure also shows trend lines obtained by fitting the modified Elashoff's model, which has also been used by others to capture emptying of different gastric components 8,[43][44][45] . It is a sigmoid shape function given by:…”
Section: B Protein Hydrolysismentioning
confidence: 79%
See 3 more Smart Citations
“…However, for all cases, initially there is an exponential rise which changes into a linear growth that eventually asymptotes to a value as t → ∞. The figure also shows trend lines obtained by fitting the modified Elashoff's model, which has also been used by others to capture emptying of different gastric components 8,[43][44][45] . It is a sigmoid shape function given by:…”
Section: B Protein Hydrolysismentioning
confidence: 79%
“…A stabilized bi-conjugate gradient method is used to solve the pressure Poisson equation. More details on the numerical methodology and grid convergence study can be found in earlier works 8,33 .…”
Section: B Fluid Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…As is common in MRI studies, the subjects were in the supine position during our experiment. Recent work highlighted the effect of body position on gastric emptying, and the effect of different volumes on gastric emptying might be different in the upright position [ 29 , 30 ]. Nonetheless, the two previously mentioned studies by Oberle et al and Wong et al were carried out mainly in the upright position, and comparable findings on the gastric emptying rates of different volumes were observed.…”
Section: Discussionmentioning
confidence: 99%